Ceropegia strophanthiflora (Apocynaceae—Asclepiadoideae)—a magnificent and rare new species from South Africa at the brink of extinction - Heiduk, Annemarie; Styles, David G.a. (Phytotaxa, 2023)
We describe a novel species of Ceropegia (Apocynaceae-Asclepiadoideae-Ceropegieae), C. strophanthiflora, from inland of Mtubatuba in northern KwaZulu-Natal, South Africa. The new species is placed in section Chamaesiphon where it appears to be vegetatively and floristically most similar to C. rehmannii (formerly Brachystelma foetidum). Ceropegia strophanthiflora can, however, be readily distinguished from this species by its strikingly colourful greenish-yellow flowers with bright purple markings and purplish-pink vibratile hairs fringing the corolla lobe bases. Most remarkable, however, are the unusually long, slender and twisted corolla lobes much reminiscent of flowers known in Strophanthus; hence the name C. strophanthiflora. There are no other known South African species exhibiting such flamboyant flowers. Concerningly, this spectacular new species may be at the brink of extinction as only very little habitat remains which is under severe anthropogenic threat. Brachystelma tanzaniense, a species with long and slender corolla lobes from Tanzania, is transferred to Ceropegia section Chamaesiphon under the proposed new name C. dodomaensis. Moreover, the blocking name for this transfer, C. tanzaniensis, is reduced to a synonym of C. cordiloba for which we designate a lectotype.